Adult ADHD Diagnostic Assessment and Treatment - Kooij, J.J. Sandra; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Adult ADHD: Diagnostic Assessment and Treatment, Third Edition covers not only diagnostic assessment, but also comorbidity patterns as well as differential diagnosis of ADHD with for example bipolar disorder and borderline personality disorder. The symptom overlap and misdiagnosis of chronic fatigue syndrome in girls and women with the inattentive subtype of ADHD, ADD is explored. The chronic delayed sleep phase syndrome associated with ADHD based on disturbances in the circadian rhythm, and the possible consequences for general health (obesity, diabetes, cardiovascular diseases and cancer) are discussed. There are sections on ADHD and intelligence, criminality, sexuality, dyslexia and autism. Adult ADHD can be treated effectively but as yet the disorder is not always recognised by professionals and this book aims to help correct this. Diagnostic tools are included, such as the structured Diagnostic Interview for Adult ADHD (DIVA), and an ultra-short and somewhat longer screening tool, all based on the DSM-IV criteria for ADHD. Treatment options cover psychoeducation and motivation and individual and group coaching; long-acting stimulants and other new drugs for treating ADHD; use of melatonin to treat the delayed sleep-phase disorder. Useful information is included on the setting up and organisation of a department for adult ADHD with a multidisciplinary team. References, websites and useful international addresses have all been updated. Adult ADHD: Diagnostic Assessment and Treatment, Third Edition is intended for students, junior doctors/residents, psychologists, psychiatrists, other mental healthcare professionals and interested parties and provides a quick overview of the current state of the science and of the methods used in diagnosis and treatment. Adult ADHD: Diagnostic Assessment and Treatment, Third Edition was originally published by Pearson Assessment and Information BV, The Netherlands.
Foreword, P. Asherson -- Foreword, A. Paternotte -- Preface -- Introduction -- Diagnostic assessment -- Diagnostic instruments -- Treatment -- Treatment: coaching adults with ADHD -- Set-up and organisation of a specialist department -- Appendix -- References -- Index -- About the author.
Keywords: Medicine; Neurology; Psychiatry; Psychopharmacology; Medicine & Public Health; Psychiatry; Psychopharmacology; Neurology